If A and B are mutually exclusive events, prove thatP(A⁄B ̅ )=(P(A))/(1-P(B))

∵P(A⁄B ̅ )=(P(A∩B ̅))/(P(B ̅))=(P(A-B))/(1-P(B))=(P(A)-P(A∩B))/(1-P(B))∵A,B mutually exclusive events→∴P(A∩B)=0∴P(A⁄B ̅ )=(P(A))/(1-P(B))

total answers (1)

start bookmarking useful questions and collections and save it into your own study-lists, login now to start creating your own collections.

∵P(A⁄B ̅ )=(P(A∩B ̅))/(P(B ̅))=(P(A-B))/(1-P(B))=(P(A)-P(A∩B))/(1-P(B))

need an explanation for this answer? contact us directly to get an explanation for this answer∵A,B mutually exclusive events→∴P(A∩B)=0

∴P(A⁄B ̅ )=(P(A))/(1-P(B))